Electrochemical synthesis and characterization of stable colloidal suspension of graphene using two-electrode cell system - Danial, Wan Hazman (AIP Publishing, 2015)
The present work reports the synthesis and characterization of graphene via electrochemical exfoliation of graphite rod using two-electrode system assisted by Sodium Dodecyl Sulphate (SDS) as a surfactant. The electrochemical process was carried out with sequence of intercalation of SDS onto the graphite anode followed by exfoliation of the SDS-intercalated graphite electrode when the anode was treated as cathode. The effect of intercalation potential from 5 V to 9 V and concentration of the SDS surfactant of 0.1 M and 0.01 M were investigated. UV-vis Spectroscopic analysis indicated an increase in the graphene production with higher intercalation potential. Transmission Electron Microscopy (TEM) analysis showed a well-ordered hexagonal lattice of graphene image and indicated an angle of 60° between two zigzag directions within the honeycomb crystal lattice. Raman spectroscopy analysis shows the graphitic information effects after the exfoliation process.